2017
DOI: 10.3892/mmr.2017.6415
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the PI3KCA pathway in circulating tumor cells and corresponding tumor tissue of patients with metastatic breast cancer

Abstract: The aim of the present study was to compare the phosphatidylinositol 3-kinase (PI3KCA)-AKT serine/threonine kinase (AKT) pathway in circulating tumor cells (CTCs) and corresponding cancerous tissues. Stemness-like circulating tumor cells (slCTCs) and CTCs in epithelial-mesenchymal transition (EMT) have been implicated as the active source of metastatic spread in breast cancer (BC). In this regard, the PI3KCA-AKT signaling pathway was demonstrated to be implicated in and to be frequently mutated in BC. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…The study was carried out at the Department of Gynecology and Obstetrics, in collaboration with the Department of Medical Oncology (for specimen recruitment), both at the University Hospital Essen, Germany and in collaboration with QIAGEN GmbH, Hilden, Germany (for library preparation and sequencing analysis). The eligibility criteria have been previously published [15]. Written informed consent was obtained from all participants at enrollment and specimens were collected using protocols approved by the institutional review board (12-5265-BO).…”
Section: Patient Population Characteristics and Eligibility Criteriamentioning
confidence: 99%
“…The study was carried out at the Department of Gynecology and Obstetrics, in collaboration with the Department of Medical Oncology (for specimen recruitment), both at the University Hospital Essen, Germany and in collaboration with QIAGEN GmbH, Hilden, Germany (for library preparation and sequencing analysis). The eligibility criteria have been previously published [15]. Written informed consent was obtained from all participants at enrollment and specimens were collected using protocols approved by the institutional review board (12-5265-BO).…”
Section: Patient Population Characteristics and Eligibility Criteriamentioning
confidence: 99%
“…While there are some studies that investigate the correlations between mutations in specific genes in CTCs and corresponding tumor tissue, trials addressing the association between mutational status of the primary tumor and the presence of CTCs are currently lacking. For example, in a study by Bredemeier et al, no correlation was observed between PI3KCA mutations in cancerous tissue and the presence of CTCs in peripheral blood (19). In another study, there was a high match rate between specific mutations in CTCs and corresponding tumor tissue, but no data regarding the association between a specific mutation and the number of CTCs were reported (18).…”
Section: Discussionmentioning
confidence: 96%
“…In a study including 216 patients, 12 genes (TP53, PIK3CA, GATA3, ESR1, MAP3K1, CDH1, AKT1, MAP2K4, RB1, PTEN, CBFB and CDKN2A) were established as significantly mutated in metastatic breast cancer (mBC), while 8 genes (ESR1, FSIP2, FRAS1, OSBPL3, EDC4, PALB2, IGFN1 and AGRN) were more frequently mutated in mBC as compared to early breast cancer (17). Several published studies have investigated the mutational status of CTCs (18)(19)(20)(21); however, data on the association between gene mutations in primary tumor tissue and the presence of CTCs in the peripheral blood are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…PI3KCA was the most mutated gene in non- NF2 tumors. Mutations in these survival genes are typically associated with therapeutic resistance and chemotherapy-induced mutagenesis [3740]. This highlights the importance of genetic assessment following surgical resection; if PI3KCA - and AKT1 -mutated tumors recur and undergo malignant progression to a higher histological grade, postoperative adjuvant treatment using known and well-characterized inhibitors should be employed, as opposed to radiotherapy or chemotherapy interventions.…”
Section: Discussionmentioning
confidence: 99%